Targeting T regulatory cells: Their role in colorectal carcinoma progression and current clinical trials. (April 2022) - Bandaru, Sai Samyuktha; Boyilla, Rajendra; Merchant, Neha; Nagaraju, Ganji Purnachandra; El-Rayes, Bassel F.
Abstract: Colorectal cancer (CRC) is classified as the third leading cancer globally and one of the major causes of morbidity and mortality around the world. The interaction of the immune system with the cancer cells plays a vital role in CRC progression. Regulatory T cells (Tregs) are a form of T cells, which regulate and suppress unwanted activation of the immune system and play a major role in preventing autoimmune diseases. Tregs exhibit a significant role in immune modulation during CRC progression through accumulation in the tumor microenvironment (TME) and suppression of immunity against tumor specific antigens promoting tumor progression. The role of Tregs in CRC progression and its interaction with other immune cells within CRC TME and current clinical trials were reviewed in this paper. Graphical Abstract: ga1 Highlights: Discusses the role of Tregs in immune modulation during CRC progression. Explores the role of Tregs in CRC tumor microenvironment. Highlights the mechanism of Tregs in CRC growth and metastasis. Identifies and discusses current clinical trials targeting Tregs in CRC therapy.